Using Glass’ Analysis Method to Improve the Students’ Speaking Skill - Kasmin Irwan (Qalam : Jurnal Ilmu Kependidikan, 2019)
This research aimed at explaining the use of Glass’ Analysis Method in improving the students’ pronunciation in speaking at the seventh grade students of SMP Negeri 1 Salomekko Kab. Bone. The researcher used pre-experimental design with one group pretest and posttest design. The population was the seventh grade students of SMP Negeri 1 Salomekko Kab. Bone., in academic year 2017/2018, which consisted of six classes. The sample was taken by purposive sampling technique and the total number of sample was 26 students. It conducted in six meetings. It was administered speaking test as instrument. The findings of the data indicated that there was significant difference between students’ post-test and pre-test.  The mean score in post-test (8.10) was greater than the mean score in pre-test (5.42). From t-test, the researcher found that the value of t-test (8.61) was greater than t-table (2.060) at the level of significance 0.05 with degree of freedom (df) = 25. Thus, the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. It means that there was a significant difference in the students’ pronunciation in speaking before and after being taught by using Glass’ Analysis Method